Factors Affecting Taxpayer Compliance (Survey on Entrepreneurs who are Bukalapak Partners in West Java) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Tax compliance is the act of a Taxpayer in fulfilling his tax obligations in accordance with the provisions of laws and regulations and taxation implementation regulations in force in a country. Taxpayer compliance can be influenced by several factors such as tax knowledge, taxpayer awareness, and the application of e-filing to carry out their obligations. The purpose of this study was to determine the effect of tax knowledge, taxpayer awareness and the application of e-filing on taxpayer compliance either partially or simultaneously. This research was conducted on shopkeepers who have been supported by an online system in partnership with Bukalapak. Respondents studied were 66 respondents with data collection instruments using questionnaires to respondents. The results showed that the knowledge of tax regulations had an effect on taxpayer compliance, taxpayer awareness had no effect on taxpayer compliance, the application of e-filing had an effect on taxpayer compliance. Simultaneously, tax knowledge, taxpayer awareness and application of e-filing have an effect on taxpayer compliance